Cantwell, Theresa Squires. Black and white photograph of woman in front of fence from Theresa Squires Cantwell's personal photograph collection. - Barrett, Terra
Eileen Squires. Photo taken in USA in the 1920s in either Melrose or Waltham, Mass.